Desenvolvimento de filmes extrusados com micropartículas de óleo essencial de orégano e aplicação na conservação de massa fresca - Balan, Geane Cristiane (2020)
The environmental impact caused by synthetic packaging has increased interest in the use of biodegradable materials. Biodegradable films can be produced using biopolymers, such as polysaccharides, proteins and lipids, forming continuous matrices that allow the incorporation of bioactive compounds. Wheat flour may be an alternative for blending with other biopolymers, such as poly (butylene adipate co-terephthalate) (PBAT), for the production of films by blown extrusion. Some additives, such as oregano essential oil, may be added to packaging as an antimicrobial and antioxidant agent to obtain active packaging. However, during the thermoplastic extrusion process, essential oils can be volatilized and even degrade and an alternative to preserve the bioactivity of these oils is to perform their microencapsulation. The objective of this work was to produce films of wheat flour and PBAT added with free and microencapsulated oregano essential oil by thermoplastic extrusion and to evaluate its applicability as an active packaging in the preservation of a brazilian fresh pastry, known as Pastel.The oregano essential oil (OEO) microparticles were produced by spray drying and characterized in terms of morphology, encapsulation efficiency, mean diameter and size distribution. The films were produced by blown extrusion process and were characterized in relation to mechanical properties, water vapor permeability (WVP), solubility, color, opacity, thermal stability, morphology and antioxidant capacity. The particles obtained showed an average diameter of 8 µm and encapsulation efficiency of 65.73%. The incorporation of microencapsulated and free OEO significantly interfered in the characteristics and properties of the film. It was found that films with microencapsulated oregano essential oil (FOM) showed lower tensile strength (T) and Young's Modulus (MY), higher elongation (ε), solubility and antioxidant capacity when compared to the others. During 28 days of refrigerated storage, Brazilian fresh pastry with FOM film presented less count of molds and yeasts, compared to pastries packed with other films. However, the same effect was not verified for the count of psychrotrophic microorganisms. The results obtained in this work suggest that microencapsulation protected OEO, allowing the development of biodegradable active films for application in foods where the contamination by fungi and yeasts is predominant.